Efektivitas Penerapan Dzikir Dalam Menurunkan Nyeri Pada Pasien Dengan Colic Abdomen - Ellyza Rahmawati; Khusnul Rohim Rufiana; Sindika Aprilia Saputri; Aprilia Anggraini Susilowati; Sri Rahayu (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Colic abdomen is abdominal pain that comes and goes, originating from organs within the abdomen, and is usually caused by infections in those organs. The clinical symptoms of colic abdomen include abdominal cramps, distension, vomiting, and pain when the abdomen is pressed. The pain associated with colic abdomen reduces focus on the surrounding environment due to the attention being centered on the pain and decreases the quality of life due to the discomfort experienced. Therefore, proper management is crucial, particularly through pain management. To gather scientific evidence on the effectiveness of implementing dzikir therapy in reducing pain levels in patients with colic abdomen. A literature study was conducted using databases such as Google Scholar, Garuda, and PubMed with article publications from 2019 to 2025. The literature search strategy involved keywords relevant to the topic and research title, using standard Boolean operators "AND" and "OR." The keywords used included: "Non-Pharmacology Therapy" OR "Spiritually" AND "Acute Pain" OR "Colic Abdomen" AND "Emergency." The analysis resulted in 5 articles discussing the application of non-pharmacological therapy, specifically dzikir therapy, which can be performed on patients experiencing pain. These studies have demonstrated positive effects in reducing pain in patients suffering from abdominal pain.